Pembelajaran Pendidikan Agama Islam terhadap Anak Tunagrahita - Sari, Prima Rosita; Istinganah, Istinganah; Alwatasi, Umar; Yusro, Wardi; Husna, Difa’ul (TSAQOFAH, 2023)
Not all children are born to be perfect human beings, but indeed no human being is perfect. However, there are children who are born with deficiencies in them. Be it his mental state or not normal. However, with this deficiency, those who have special needs are not hindered from continuing to carry out the laws that God has set for each of his servants, regardless of the background of every human being. They also have the right to education in general. And this is the task of Islamic education itself to provide the best for children with special needs. Helping to develop potential, skills, physical, moral, and so on. The teachings developed by Islamic education itself must also be adapted to the abilities of children with special needs. As is the case in this study, the researcher conducted a qualitative model study by conducting interviews and documentation as well as narrowing down the information obtained during the interviews. The purpose of this study is to find out the Islamic religious learning system for mentally retarded children. In this study, more specifically towards mentally retarded children where they have relatively low thinking abilities. Thus, teachers must take the initiative to teach Islamic education material that can be grasped by mentally retarded children. Like, providing ablution videos. In order to provide an understanding of mental retardation and practice and not just theory. Therefore, communication in learning also needs repetition of its explanation. This is due to the limitations of mentally retarded children in processing compound sentences.